PENGUMUMAN IDENTITAS SEBAGAI HUKUMAN TAMBAHAN TERHADAP PELAKU PEDOFILIA DI PERADILAN INDONESIA - Andrio Chris Waldi Pasaribu; Emilda Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the problems faced by the Indonesian people today is the crime of sexual violence. Pedophilia as a sexual orientation by liking minors. As a distorted orientation and contrary to applicable norms. Pedophile behavior often leads to sexual violence. Based on the characteristics that exist that the ability to seduce a reliable pedophilia that can deceive children and the nature of pedophiles who love to move locations cause this to make it not an ordinary crime. Very often cases of pedophile crime appear and are revealed after the number of victims who report. The effects of pedophilia crimes lead to mental trauma, genital and rectal injuries and the potential to be a future offender for victims for boys. In Government Regulation in Lieu of Law Number 1 of 2016 on the second amendment of Law No. 23 of 2002 Regarding child protection, it allows additional penalties to announce the identity of the offender. as a form of deterrent effect and protection to the community, but there is no formal criminality in the form of implementation so that the ideal concept is needed so that additional punishment can be carried outThis type of research is a normative legal research that is using literature study in finding data. This research is descriptive in nature which tries to provide detailed and detailed data on the existing problems. In writing this research using qualitative data analysis which means explaining and concluding about the data that has been collected by the author. This study uses secondary data or scientific data that has been codified.The results of this study are to explain that the material penalties for additional sentences announcing the identity of the perpetrators have been clearly regulated. but for formal criminal arrangements have not been clearly regulated. thus causing additional punishment is not perfect. The author provides an ideal concept in the form of announcements of identity given to the public through mass media, print and social media, Announcement of identity is also given to educational institutions and the Ministry of Law and Human Rights. announcements of identity are also given through the website managed by the Indonesian child protection commission. Announcement of identity is done in order to reduce the level of pedophile crime and provide protection for children and society.Keywords: Announcement Of The Identity Of The Offender - Additional Punishment - Pedophilia.